The Biomarkers of Cd4+ T Regulatory Cells Associated with Tumour Immune Escape - Nyaribari MC (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2020)
Objective: In this review, we endeavor to do a literature search mainly focusing on keywords CD4+FOXP3+, CD4+CD127-, CD4+CD39+, CD4+LAP+ cancer immunotherapy, cancer immunotherapy strategies and articles published between 2015 to 2019 to add onto the minimal definition of human Treg, by an international workshop organized by collaborative immunoguiding program. Methodology: In this review, we highlight the antitumor suppressive biomarkers of CD4+ Treg cells, how they suppress the immune response.  Summary: The biomarkers play a role in designing of cancer immunotherapy to overcome resistance and enhance anti-tumor immune response among late-stage cancer patients who have exhausted the standard of care. There is evidence suggesting that a combination of treatment strategies has enhanced immune responses for some patients who have developed or are resistant to monoclonal immunotherapy treatments.